Social and Individual-Psychological Factors of an Individual’s Propensity for Corrupt Behavior - Zarichanskyi , Oleh (Insight: the psychological dimensions of society, 2024)
The article presents the results of a study of social and psychological elements associated with corrupt behavior. The aim of the study is to analyze the social and individual-psychological factors associated with corrupt actions and to investigate the relationship between the Dark Triad traits and an individual’s propensity for corrupt behavior. Methods: The Short Dark Triad questionnaire by D. Paulhus and K. Williams (2002), A. Furnham “Money Attitude and Behaviour Scale” (modified version by M. Simkiv (2012) “Money Perceptions and Behavior Scale”). Results. Power, the characteristics of a corrupt person (egocentrism, lack of guilt), moral traits (manipulativeness, tendency to use others to further one’s own goals), self-esteem traits (negative self-esteem or guilt), and a variety of individual personality traits (such as Machiavellianism, narcissism, and psychopathy) are all proven to be causes of corrupt behavior. Empirical research has demonstrated a relationship between the Dark Triad qualities and various money attitudes, which in turn enables the prediction of corrupt conduct proclivity. The Dark Triad characteristics have been shown to be predictive of financial manipulation and anxiety. Discussion and conclusions: It is clarified that maladaptive moral dysfunction, a lack of empathy, the pursuit of profit, an urge for control and power, a low degree of fear of punishment, and the impacts of group influence are the social, psychological, and individual components of corrupt behavior. These variables, together with cultural, social, and economic variables, influence how likely it is for someone to engage in corrupt activity. A tendency toward corrupt behavior is also linked to aspects of money behavior and the Dark Triad qualities. Research indicates that persons with a strong Machiavellian streak are more likely to employ financial tactics and behaviors that include manipulating or taking advantage of others. Narcissists frequently use enrichment to increase their sense of self-worth. Psychopaths’ lack of empathy and capacity for taking advantage of others makes them more likely to make hazardous financial judgments and to manipulate money.